Progression of chronic kidney disease: comparative analysis of glomerular filtration rate in patients with hypertension and/or diabetes mellitus (Research, Society and Development, 2022)
The human kidney has several functions that must be in balance and harmony for the proper functioning of the body. To evaluate individual renal function, one can calculate the glomerular filtration rate through several formulas, among which we highlight Ckd-Epi and MDRD. Several comorbidities are associated with renal dysfunction, such as hypertension and diabetes mellitus, and the progression of renal dysfunction directly impacts the quality of life of the patient. The present qualitative, exploratory, retrospective, and observational study aimed to identify the comorbidities in selected patients as well as the stratification of renal function based on the Ckd-Epi formula. Furthermore, the aim of this article is to compare the glomerular filtration rate in patients with chronic kidney disease associated with hypertension and/or diabetes mellitus over the time period studied. The data present in this study were taken from electronic medical records present in the IPM health system of patients seen by the public health system of Cascavel/PR. Thus, these data were submitted to Database Knowledge Discovery (DCAB) and variance analysis tests, with significance of α=0.05. The studies showed an average reduction in glomerular filtration rate of 11.44%. At the end of the study, pressure control was established as an important criterion to prevent progression of chronic kidney disease. Furthermore, no renal worsening was related to the increased glycemic levels in the observed group.